2012
DOI: 10.1021/je3006166
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–Liquid Equilibria for the System Water + 4-Methylpentan-2-one + Acetic Acid at Several Temperatures

Abstract: The effect of temperature on the liquid–liquid equilibrium (LLE) of the ternary system of {water (1) + acetic acid (2) + 4-methylpentan-2-one (3)}, a recommended system for liquid–liquid extraction studies, was investigated at (288.2, 313.2, and 333.2) K. The reliability of the experimental tie line data was examined with the Othmer–Tobias and the Hand correlations that represented an excellent agreement. The distribution coefficient of acetic acid between organic and aqueous phases increases significantly wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…For example Saien and Daliri [46] who have used a cumene-isobutyric acid-water and Saien et al [47] who have used (4-methylpentan-2-one)-acetic acid-water have found that the distribution coefficients increased as temperature increased by 3.02%/°C and 1.84%/°C respectively, which are comparable to the results obtained in this study. Table 4 3.…”
Section: Distribution Coefficientssupporting
confidence: 88%
“…For example Saien and Daliri [46] who have used a cumene-isobutyric acid-water and Saien et al [47] who have used (4-methylpentan-2-one)-acetic acid-water have found that the distribution coefficients increased as temperature increased by 3.02%/°C and 1.84%/°C respectively, which are comparable to the results obtained in this study. Table 4 3.…”
Section: Distribution Coefficientssupporting
confidence: 88%
“…The experimental tie-line data were correlated by using the Aspen Plus (Version 8.4) data regression tool for both the NRTL and the UNIQUAC models. This software employs an objective function, called “Britt-Luecke”, to find model parameters . The obtained NRTL and UNIQUAC coefficients of the equations for binary interaction parameters in this work are listed in Table .…”
Section: Resultsmentioning
confidence: 99%
“…This software employs an objective function, called "Britt-Luecke", to find model parameters. 31 The obtained NRTL and UNIQUAC coefficients of the equations for binary interaction parameters in this work are listed in Table 5.…”
Section: Measurementsmentioning
confidence: 99%
“…In case of acetic acid, MIBK has been studied earlier by Saien and TAA by Fahim and Al-Muhtaseb . Their measured data can be used to calculate distribution coefficient and selectivity of the solvent for acetic acid.…”
Section: Resultsmentioning
confidence: 99%
“…In case of acetic acid, MIBK has been studied earlier by Saien 23 and TAA by Fahim and Al-Muhtaseb. 24 Their measured 6).…”
Section: ■ Introductionmentioning
confidence: 99%